2011
DOI: 10.1074/jbc.m110.200857
|View full text |Cite
|
Sign up to set email alerts
|

NBA1/MERIT40 and BRE Interaction Is Required for the Integrity of Two Distinct Deubiquitinating Enzyme BRCC36-containing Complexes

Abstract: BRCC36-deubiquitinating enzyme (DUB) forms two different complexes through interactions with two different adaptor proteins Abraxas and ABRO1 in cells.Abraxas mainly localizes in the nucleus, mediating the interaction of BRCC36 with BRCA1. ABRO1 is mainly localized in the cytoplasm. Because it lacks the BRCA1-interacting motif, the ABRO1 complex does not interact with BRCA1. Both BRCC36-containing complexes contain common components including BRE and NBA1/MERIT40. Here, we found that the two complexes are asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 39 publications
3
90
0
Order By: Relevance
“…Although the regulatory basis of its DUB activity is beginning to be understood (3)(4)(5)(6)34), it has remained unknown whether the BRCC36 ubiquitin hydrolyzing activity plays a role in mammalian DNA damage responses. In this study, we have systematically examined, by adopting both RNAi and genome editing approaches, whether BRCC36 and its DUB may be functionally important in driving cellular response to DSBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the regulatory basis of its DUB activity is beginning to be understood (3)(4)(5)(6)34), it has remained unknown whether the BRCC36 ubiquitin hydrolyzing activity plays a role in mammalian DNA damage responses. In this study, we have systematically examined, by adopting both RNAi and genome editing approaches, whether BRCC36 and its DUB may be functionally important in driving cellular response to DSBs.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study also revealed that an additional phosphorylation event in the vicinity of pSPXF (serine 404) further stabilizes the Abraxas-BRCA1 interaction by formation of a stable dimer (16). Other components of the BRCA1-A complex, including Merit40 and BRE, are also key in maintaining the integrity of the macromolecular protein complex (6,9,17,18) and for BRCA1 accumulation at DSB sites. Together, these data underscore critically important roles of each of the subunits that make up the protein assembly.…”
Section: Active Hydrolysis Of Ubiquitin Polymers By Deubiquitylases (mentioning
confidence: 99%
See 1 more Smart Citation
“…BRCC36 DUB activity and localization are regulated via its interactions within the context of each protein complex. In the BRCA1-A complex, ABRA1 and BRE are essential for BRCC36 DUB activity and localization at DNA damage site (100,122,127,128). Although the exact function of BRCC36 deubiqutination at DNA damage site is not known, it has been suggested that BRCC36 catalyzes the deubiquitination of chromatin-associated proteins that lead to the chromatin remodeling and amplification of damage signal.…”
Section: Recruitment Of Brca1-a Complex To Dna Damage Sites By Rnf8/rmentioning
confidence: 99%
“…Aside from RAP80 and BRCA1/BARD1, many components of the BRCA1-A complex possess structural domains implicating them in ubiquitination pathway. BRCC36 has a JAM domain characteristic of lysine 63-specific deubiquitinating enzymes, and Abraxas and BRE contain predicted Mpr-1/Pad1 N-terminal (MPN -) and ubiquitin E2 variant (UEV) domains respectively (122,(125)(126)(127)(128). Possible targets of BRCC36 include RAP80 and di-ubiquitinated H2A/H2AX.…”
Section: Recruitment Of Brca1-a Complex To Dna Damage Sites By Rnf8/rmentioning
confidence: 99%